When is coffee not coffee? Luigi Ferdinando Marsigli's depictions of the coffee plant in “Notizie, di Costantinopoli; sopra la pianta del caffè” (1703) - Fernando E. Vega; Aaron P. Davis (Italian Botanist)
The late 17th and early 18th centuries were an era in which the coffee drink was first becoming known throughout Europe, and there was a strong interest in disseminating what the plant looked like through the use of botanical illustrations. In 1685, Luigi Ferdinando Marsili published a coffee-related treatise entitled “Bevanda asiatica”. This was followed in 1703 with the publication of the monograph “Notizie, di Costantinopoli; sopra la pianta del caffè”. “Bevanda asiatica” conveys interesting information on a coffee-related manuscript acquired by Marsigli in Constantinople (present day Istanbul), as well as knowledge he gained as a slave of the Ottoman empire, when he was tasked with making coffee. “Notizie, di Costantinopoli ”includes various engravings supposedly depicting coffee plants. We present the original watercolors used to create the engravings in “Notizie, di Costantinopoli”and present evidence for the first time since publication, 322 years ago, demonstrating that none of the engravings depict coffee plants.